Scope of mean neutrophil volume as an indicator of neonatal sepsis - Chaitra B E; Raja Parthiban; Shilpa G; Indrani Krishnappa; Impana Gowda (Journal of Pathology of Nepal)
Background: Neonatal sepsis is one of the leading causes of mortality in developing countries because of its non-specific presentation. Blood culture is the gold standard for diagnosing sepsis, but culture results take 48 – 72 hours. Therefore, there is a need for an indicator that could be used as a simple parameter to indicate the possibility of evolving sepsis to the clinician. The efficacy of mean neutrophil volume as an indicator must be evaluated.